A pilot study of combination anti-cytokine and anti-lymphocyte biological therapy in rheumatoid arthritis. - Morgan, A; Hale, G; Rebello, P; Richards, S; Gooi, H; Waldmann, H; Emery, P; Isaacs, J (2008)
BACKGROUND: Immunological tolerance in humans using anti-T-cell monoclonal antibodies (mAbs) may be hampered by a pro-inflammatory microenvironment. All clinical trials of such therapies in rheumatoid arthritis (RA), however, have selected patients with active disease at baseline. Concurrent neutralization of inflammation with a TNFalpha antagonist should maximize the potential of anti-T-cell mAbs to induce tolerance in RA. AIM: To evaluate the safety of combining a TNFalpha antagonist and CD4 mAb in RA. DESIGN: An iterative pilot study focused on the safety of such combination therapy. METHODS: Eight poor prognosis, seropositive RA patients were treated with combined CD4 and TNFalpha blockade. Prolonged CD4 blockade was achieved with a humanized mAb, and TNFalpha blockade with a p55 TNF receptor fusion protein. RESULTS: There was a low incidence of classical first-dose reactions to the CD4 mAb, possibly reflecting concomitant TNFalpha blockade. An unusual anaphylactoid reaction was seen, however, and one patient developed a probable allergic reaction after several infusions. Skin rashes were common, as previously reported with CD4 mAb monotherapy. No serious infections were documented during follow-up, despite CD4+ lymphopenia in some patients. Most patients appeared to demonstrate improved RA disease control after the study. After 17-49 months after therapy, one patient was in remission, one remained off disease modifying anti-rheumatic drugs and five had stable disease, three on previously ineffective doses of methotrexate. CONCLUSION: We report, for the first time in man, immunotherapy with a combination of an anti-cytokine and an anti-T-cell reagent. We witnessed an unusual first-dose reaction but there were no significant infectious complications.